2008
DOI: 10.1086/592252
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Amplification of Drug Resistance among Previously‐Treated Patients with Tuberculosis in Kampala, Uganda

Abstract: The burden of drug resistance in previously treated patients with TB in Uganda is sizeable, and the risk of generating additional drug resistance is significant. There is an urgent need to improve the treatment for such patients in low-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 21 publications
2
74
5
Order By: Relevance
“…Similar to our study, Temple et al 2008, had shown that 28.1% of M. tuberculosis isolates were resistant to at least one anti-TB drug and 71.9% isolates were sensitive to all four drugs. 16 Among 31 resistant isolates, 11 (35.5%) were mono resistant and 20 (64.5%) were poly resistant. Combined drug resistant was more prevalent in relapse cases visiting NTC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our study, Temple et al 2008, had shown that 28.1% of M. tuberculosis isolates were resistant to at least one anti-TB drug and 71.9% isolates were sensitive to all four drugs. 16 Among 31 resistant isolates, 11 (35.5%) were mono resistant and 20 (64.5%) were poly resistant. Combined drug resistant was more prevalent in relapse cases visiting NTC.…”
Section: Discussionsupporting
confidence: 90%
“…The relapse PTB was 45.5% which was less than study reported earlier (57%). 16 In this study, relapse was higher in males (n=89, 70%) than female (n=38, 29.9%). Higher cases of relapse were also seen in a study done by Soomro and Quazi, 2009 which reported that 62% were males and 38% were females.…”
Section: Discussionmentioning
confidence: 46%
“…If so, this could explain the fact that the rates of resistance to any drug and multidrug resistance were higher in our study. In the literature, the reported rates of normal chest X-rays in patients with smear-or culture-positive PTB are low, (4,11,13,22,24) except in HIV-infected patients. (8) A prevalence survey conducted in Cape Town, South Africa revealed that the presence of any abnormalities on chest X-ray has a high sensitivity for detecting subjects with smear-or culture-positive tuberculosis (0.97%; 95% CI: 0.90-1.00).…”
Section: Discussionmentioning
confidence: 96%
“…(6,13,(19)(20)(21)(22) However, the mean ages reported for PTB patients treated at However, the number of cases of re-treatment was more than twice as high among the patients with bilateral involvement. After the first month of treatment, the proportion of patients with positive cultures was significantly greater in antituberculosis treatment was self-reported in our study, the rates of relapse (12.1%) and re-treatment (12.3%) might represent underestimations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation